Transformational Leadership Boosts Job Satisfaction and OCB Among BPS Employees: Kepemimpinan Transformasional Meningkatkan Kepuasan Kerja dan OCB Pegawai BPS - Mardanillah, Jihan Faizatul Rahma; Marwan, Marwan; Jannang, Abdul Rahman (Indonesian Journal of Innovation Studies, 2024)
General background:In a dynamic world of work today, where more and more tasks have to be carried out in teams, employees are required to be able to work more flexibly and help the others in their team. This behavior is called organizational citizenship behavior (OCB). Specific background: OCB will appear when employees feel satisfied with the work they have. There are several leadership styles that can influence the growth of OCB behavior and job satisfaction felt by employees, one of which is the transformational leadership style. Aims:This study aims to determine whether there is a relationship between transformational leadership style and organizational citizenship behavior, mediated by job satisfaction among BPS employees in the North Maluku Province region using SEM-PLS. Results: Primary data was collected from a sample of 158 employees. The research results show that the transformational leadership style has a positive and significant effect both directly on employee OCB and indirectly mediated by employee job satisfaction variables.Novelty: highlights the key role of job satisfaction on OCB. Implications:Reccomends to pay attention to employee satisfaction and needs at work Highlights: Transformational leadership significantly enhances employee job satisfaction and OCB. Job satisfaction mediates the relationship between transformational leadership and OCB. Effective leadership styles are essential for fostering a positive work environment and maximizing employee contributions. Keywords: Organizational Citizenship Behavior (OCB), Job Satisfaction, Transformational Leadership, Central Bureau of Statistics